Laparoscopic radical hysterectomy: A safe and effective surgical treatment for early-stage cervical cancer - Subedi, Nilam; Ghimire, Asmita; Shrestha, Asmita; Pant, Samriddha Raj; Pant, Padam Raj (Grande Medical Journal, 2021)
Background: Laparoscopic techniques to treat early stage cervical cancer have been recently begun by gynecologic oncologist. The aim of our study was to retrospectively evaluate the oncological outcomes of laparoscopic radical hysterectomy for early stage cervical cancer.Methods: A retrospective review of medical records was performed to identify patients who underwent laparoscopic radical hysterectomy. Data was obtained from the medical record department and analyzed.Result: Laparoscopic radical hysterectomy was done in nine patients in a period of last 1.5 yrs. The mean age was 50.2 years and BMI was 24.29 respectively. Most of the cases (5) of were stage l followed by stage ll in four cases. Five patients had attained menopause while four were having normal menstrual cycle. Average blood loss during surgery was 200 ml with mean surgery time of 3.8 hrs. Most of the patients were discharged in 5 days however one had longest hospital stay of 10 days. Histopathological report of four patients showed adenocarcinoma and five had squamous cell carcinoma. None of the patients had positive lymph node. One patient had right iliac vein injury during surgery.Conclusions: Laparoscopic radical hysterectomy provides excellent oncologic outcome to patients with early stage cervical cancer.